2018
DOI: 10.3390/jmse6020043
|View full text |Cite
|
Sign up to set email alerts
|

Coupling Numerical Methods and Analytical Models for Ducted Turbines to Evaluate Designs

Abstract: Hydrokinetic turbines extract energy from currents in oceans, rivers, and streams. Ducts can be used to accelerate the flow across the turbine to improve performance. The objective of this work is to couple an analytical model with a Reynolds averaged Navier-Stokes (RANS) computational fluid dynamics (CFD) solver to evaluate designs. An analytical model is derived for ducted turbines. A steady-state moving reference frame solver is used to analyze both the freestream and ducted turbine. A sliding mesh solver i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 17 publications
(41 reference statements)
0
21
0
Order By: Relevance
“…Qualification of a specific accelerator's performance is necessary to model non-ideal states and to benchmark a particular geometry. The Thrust Model [15] satisfies these requirements.…”
Section: The Thrust Modelmentioning
confidence: 87%
See 3 more Smart Citations
“…Qualification of a specific accelerator's performance is necessary to model non-ideal states and to benchmark a particular geometry. The Thrust Model [15] satisfies these requirements.…”
Section: The Thrust Modelmentioning
confidence: 87%
“…We show that the Thrust Model is related to Rankine-Froude's Momentum and Actuator Disk Theory [15] and thereby Betz's Law [9] with additional constraints. When related to the Coefficient of Thrust (CT) and the area ratio between the throat and maximum area is set to one, Rankine-Froude momentum theory's wake velocity equation is the same as the Thrust Model's disk velocity equation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, they investigated several types of HAHT [5,7,8], and the results showed that the maximum power coefficient has significantly improved. The investigation of HAHT is still a hot topic all over the world [9,10].…”
Section: Introductionmentioning
confidence: 99%